The fountain of age - Friedan, Betty (Simon & Schuster, 1993)
In 1963, Betty Friedan's transcendent work, The Feminine Mystique, changed forever the way women thought about themselves and the way society thought about women. In 1993, with The Fountain of Age, Friedan changes forever the way all of us, men and women, think about ourselves as we grow older and the way society thinks about aging. Struggling to hold on to the illusion of youth, we have denied the reality and evaded the new triumphs of growing older. We have seen age only as decline. In this powerful and very personal book, which may prove even more liberating than The Feminine Mystique, Betty Friedan charts her own voyage of discovery, and that of others, into a different kind of aging. She finds ordinary men and women, moving into their fifties, sixties, seventies, discovering extraordinary new possibilities of intimacy and purpose. In their surprising experiences, Friedan first glimpsed, then embraced, the idea that one can grow and evolve throughout life in a style that dramatically mitigates the expectation of decline and opens the way to a further dimension of "personhood." The Fountain of Age suggests new possibilities for every one of us, all founded on a solid body of startling but little-known scientific evidence. It demolishes those myths that have constrained us for too long and offers compelling alternatives for living one's age as a unique, exuberant time of life, on its own authentic terms. Age as adventure! In these pages, film producers and beauticians, salespersons and college professors, union veterans and business tycoons, former (and forever) housewives, male and female empty-nesters and retirees, have crossed the chasm of age ... and kept going. They have found fulfillment beyond career, bonding that transcends youthful dreams of happily-ever-after, and a richer, sweeter intimacy not tied to mechanical measures of sexual activity, but to deep and honest sharing. While gerontologists focus on care, illness, and the concept of age as deterioration, Friedan sets out to separate the complex actualities of biological aging from its pathologies. She distinguishes what is programmed and irreversible from what remains viable and open to choice and transformation. She demonstrates how important to human vitality after sixty is our own control over our lives. She sheds welcome new light on the nursing home specter, the current brouhaha over menopause, and the new intergenerational warfare. She suggests revolutionary ideas about health care, housing, and work and new uses for the wisdom of age in the evolution of our whole society. The Feminine Mystique is universally regarded as the catalyst for the modern women's movement. In The Fountain of Age, Betty Friedan breaks through the mystique of age-as-problem, and proposes a new Movement of women with men, old with young, that will transform our society.